Determinants Of Indonesia's Pineapple Exports In 2013-2023 - Gresy Bebi Ananda Br Sembiring; Anak Agung Bagus Putu Widanta (International Journal of Economics, Management and Accounting, 2025)
Pineapple is one of Indonesia's top three fruit commodities in terms of production volume. In 2022, Indonesia became the world's largest pineapple producer. Pineapple production in Indonesia has fluctuated but has generally shown an increasing and stable trend from 2013 to 2023, with expectations of continued growth. This study aims to analyze the influence of production, the wholesale price index, exchange rates, and export prices on Indonesia's pineapple export volume from 2013 to 2023. This research utilizes secondary time-series data on a quarterly basis, analyzed using multiple linear regression and classical assumption tests. The results indicate that production, the wholesale price index, exchange rates, and export prices simultaneously influence Indonesia's pineapple export volume. Partially, production and exchange rates have a positive but statistically insignificant effect on export volume, while the wholesale price index and export prices have a negative yet statistically significant impact. These findings highlight the importance of policies that can reduce production costs to enhance the competitiveness of Indonesian pineapples in the international market. Through synergy between the government, exporters, and farmers, it is expected that Indonesia's pineapple exports will continue to grow sustainably.